Multiple receptors coupled to phospholipase C gate long-term depression in visual cortex - Choi, SY; Chang, J; Jiang, B; Seol, GH; Min, SS; Han, JS; Shin, HS; Gallagher, M; Kirkwood, A (SOC NEUROSCIENCE, 2005)
Long-term depression (LTD) in sensory cortices depends on the activation of NMDA receptors. Here, we report that in visual cortical slices, the induction of LTD ( but not long-term potentiation) also requires the activation of receptors coupled to the phospholipase C (PLC) pathway. Using immunolesions in combination with agonists and antagonists, we selectively manipulated the activation of alpha 1 adrenergic, M1 muscarinic, and mGluR5 glutamatergic receptors. Inactivation of these PLC-coupled receptors prevents the induction of LTD, but only when the three receptors were inactivated together. LTD is fully restored by activating any one of them or by supplying intracellular D-myo-inositol-1,4,5- triphosphate (IP3). LTD was also impaired by intracellular application of PLC or IP3 receptor blockers, and it was absent in mice lacking PLC beta 1, the predominant PLC isoform in the forebrain. We propose that visual cortical LTD requires a minimum of PLC activity that can be supplied independently by at least three neurotransmitter systems. This essential requirement places PLC-linked receptors in a unique position to control the induction of LTD and provides a mechanism for gating visual cortical plasticity via extra-retinal inputs in the intact organism.
Keywords: METABOTROPIC GLUTAMATE RECEPTORS; EXPERIENCE-DEPENDENT PLASTICITY; OCULAR DOMINANCE PLASTICITY; KITTEN STRIATE CORTEX; RAT PREFRONTAL CORTEX; DHPG-INDUCED LTD; SYNAPTIC PLASTICITY; CORTICAL PLASTICITY; AREA CA1; DEVELOPMENTAL PLASTICITY